Everyday Entrepreneurship—A Call for Entrepreneurship Research to Embrace Entrepreneurial Diversity - Welter, Friederike; Baker, Ted; Audretsch, David B.; Gartner, William B. (Entrepreneurship Theory and Practice, 2017)
This essay contrasts a perspective that places an excessive focus on technology businesses and growth with a view of entrepreneurship that embraces its heterogeneity. We challenge a taken–for–granted belief that only certain kinds of entrepreneurship might lead to wealth and job creation and additionally suggest that these two outcomes (wealth and job creation) need to be placed within a broader context of reasons, purposes, and values for why and how entrepreneurship emerges. We suggest that a wider and nondiscriminatory perspective on what constitutes entrepreneurship will lead to better theory and more insights that are relevant to the phenomenon.